2021
DOI: 10.3390/toxins14010015
|View full text |Cite
|
Sign up to set email alerts
|

The Prescription of Drugs That Inhibit Organic Anion Transporters 1 or 3 Is Associated with the Plasma Accumulation of Uremic Toxins in Kidney Transplant Recipients

Abstract: The renal elimination of uremic toxins (UTs) can be potentially altered by drugs that inhibit organic anion transporters 1/3 (OAT1/OAT3). The objective of the present study was to determine whether the prescription of at least one OAT1/OAT3 inhibitor was associated with the plasma accumulation of certain UTs in kidney transplant recipients. We included 403 kidney transplant recipients. For each patient, we recorded all prescription drugs known to inhibit OAT1/OAT3. Plasma levels of four UTs (trimethylamine N-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 60 publications
0
10
1
Order By: Relevance
“…23,24 Furosemide itself has been recognized to increase the levels of several highly associated metabolites in human patients. 20 Taken together, the mechanistic concordance suggests that many identified solute levels are at least partially determined by proximal tubular organic anion clearance and therefore may be useful as functional biomarkers.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…23,24 Furosemide itself has been recognized to increase the levels of several highly associated metabolites in human patients. 20 Taken together, the mechanistic concordance suggests that many identified solute levels are at least partially determined by proximal tubular organic anion clearance and therefore may be useful as functional biomarkers.…”
Section: Discussionmentioning
confidence: 87%
“…8 Furosemide in particular has long been recognized as a specific substrate for OAT1/3 both in vitro and in vivo, with apical transport provided by multidrug resistance protein 4 similar to many uremic solutes; however, most solutes will have some affinity for multiple transporters. [18][19][20][21] As such, heterogeneity of tubular transport systems likely precludes a single gold standard marker of secretory clearance.…”
Section: Discussionmentioning
confidence: 99%
“…Granados et al (2021) verified that a cohort of 20 human subjects treated with probenecid had elevated levels of tryptophan-derived metabolites, including IS and kynurenine [ 111 ]. In a cohort of kidney transplant patients, André et al (2022) demonstrated that patients with a prescription of at least one drug which inhibits OAT1/OAT3 ( n = 311) had higher plasma levels of IS, PCS, and IAA, but no difference in TMAO levels compared to patients without a prescription of OAT inhibitors ( n = 92) [ 112 ]. The authors also showed a significant accumulation of PCS in patients with OAT-inhibiting drug prescriptions than in those without, even adjusting parameters for age, renal function, transplant time, and plasma albumin levels by multivariate analysis [ 112 ].…”
Section: Cell Membrane Transporters Of Uremic Toxinsmentioning
confidence: 99%
“…In a cohort of kidney transplant patients, André et al (2022) demonstrated that patients with a prescription of at least one drug which inhibits OAT1/OAT3 ( n = 311) had higher plasma levels of IS, PCS, and IAA, but no difference in TMAO levels compared to patients without a prescription of OAT inhibitors ( n = 92) [ 112 ]. The authors also showed a significant accumulation of PCS in patients with OAT-inhibiting drug prescriptions than in those without, even adjusting parameters for age, renal function, transplant time, and plasma albumin levels by multivariate analysis [ 112 ]. Together, these data indicate that drug pharmacokinetics may affect the transport of uremic toxins involving OATs, which highlights the need to understand the interaction of transporters with these drugs and the uremic toxins, especially in CKD.…”
Section: Cell Membrane Transporters Of Uremic Toxinsmentioning
confidence: 99%
“…A few studies have shown that the inhibition of OAT1/OAT3 transporters (whether renal or neuronal) induces the accumulation of UTs [7,8,12]. For example, an in vivo study in rats demonstrated that the administration of ciprofloxacin decreased the renal clearance of IS [13].…”
Section: Introductionmentioning
confidence: 99%